The selective inversion technique in aeronautical structural dynamics. - Pedro Paulo Antunes Novo (2001)
The selective inversion technique in structural dynamics is presented. Plate and shell models under different constrains are presented and are compared with analytical results for validation and performance analysis. Complex aeronautical structures represented by a rear fuselage model is simulated and checked by finite element models. Conclusion based on accuracy and computational efforts are presented stemming on versatility and advantages in the eigenvalues extraction in dynamic analysis.